Modlitwa i gestyka religijna w poezji Jesienina - Szokalski, Jerzy (Studia Rossica Posnaniensia, 2012)
The theme of this essay is to present some religious practices in the lyric poetry of Sergei Yesenin, especially the rites of the Orthodox Church along with many accompanying manifestations of the spiritual life and all kinds of gestures (mostly very distant) associated with the sphere of human religiosity. The author stresses the autonomy of the Orthodox Church as a way of perceiving the world and the mystical communion with it. This communication takes place primarily at the level of language, and particularly at the level of body language and the gestures of the language that could (although, as emphasized, not always) express the certain intentions and feelings of a religious entity as well as quasi-ritual or ceremonial speech acts: invocations, prayers, veneration, etc., but seen in some isolation from their religious functions.